Health-related quality of life with belzutifan versus everolimus for advanced renal cell carcinoma (LITESPARK-005): patient-reported outcomes from a randomised, open-label, phase 3 trial - Powles, Thomas; Choueiri, Toni K; Albiges, Laurence; Peltola, Katriina; de Velasco, Guillermo; Burotto, Mauricio; Suarez, Cristina; Ghatalia, Pooja; Iacovelli, Roberto; Lam, Elaine T; Verzoni, Elena; Gümüş, Mahmut; et al. (The Lancet. Oncology, 2025)
BACKGROUND: The first-in-class hypoxia-inducible factor-2α (HIF-2α) inhibitor belzutifan is approved for patients with advanced renal cell carcinoma previously treated with immune checkpoint and anti-angiogenic therapy based on results of the phase 3 LITESPARK-005 trial. We present patient-reported outcomes (PROs) from LITESPARK-005. METHODS: LITESPARK-005 was an open-label, multicentre, randomised, active-controlled phase 3 trial conducted at 147 hospitals and cancer centres in six regions. Eligible participants were 18 years or older with advanced clear cell renal cell carcinoma, had a Karnofsky Performance Status score of 70% or higher, had measurable disease per Response Evaluation Criteria in Solid Tumours (RECIST) version 1.1, had disease progression on or after treatment with anti-PD-1 or anti-PD-L1 immunotherapy and a VEGF tyrosine kinase inhibitor (in sequence or in combination), and had received no more than three previous systemic lines of therapy. Eligible participants were randomly assigned (1:1) centrally using interactive voice-response and web-response systems to receive either belzutifan 120 mg orally once daily or everolimus 10 mg orally once daily. Randomisation was stratified by International Metastatic Renal Cell Carcinoma Database Consortium prognostic score and number of previous VEGF-targeted or VEGF receptor-targeted therapies. The dual primary outcomes were progression-free survival and overall survival, results of which have been reported previously. In this study, prespecified secondary patient-reported outcomes (PROs) from LITESPARK-005 were assessed using the Functional Assessment of Cancer Therapy-Kidney Cancer Symptom Index: Disease Related Symptoms (FKSI-DRS) and the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30). The PRO analysis population included all participants who received at least one dose of study therapy and completed at least one PRO assessment. Least-squares mean change from baseline in PROs at week 17 was assessed using a constrained longitudinal data analysis model. Time to deterioration in physical functioning (prespecified) and role functioning (post hoc), as assessed by the EORTC QLQ-C30, were also evaluated in the PRO analysis population. This trial is ongoing, closed to recruitment, and registered with ClinicalTrials.gov, NCT04195750. FINDINGS: Between March 10, 2020, and Jan 19, 2022, 996 participants were screened for eligibility and 746 participants were randomly assigned to belzutifan (n=374) or everolimus (n=372). The PRO full analysis set population included 366 participants in the belzutifan group and 354 in the everolimus group. Median time from randomisation to the database cutoff date (June 13, 2023) was 25·7 months (IQR 21·7-30·4). Completion rates for FKSI-DRS and QLQ-C30 were higher than 94% at baseline and higher than 55% at week 17 in each group. Change from baseline to week 17 in FKSI-DRS score (difference in least-squares mean between groups 1·5 [95% CI 0·7 to 2·2]) and QLQ-C30 global health status-quality of life (QOL) score (6·4 [3·2 to 9·6]) suggested stability with belzutifan versus worsening with everolimus. Change from baseline to week 17 was similar between groups for QLQ-C30 physical functioning (difference in least-squares mean 2·5 [95% CI -0·6 to 5·5]) and QLQ-C30 role functioning (4·2 [0·1 to 8·4]) subscale scores. Time to deterioration was similar between the belzutifan and everolimus groups for EORTC physical functioning (median 19·3 months [95% CI 11·1 to not reached] in the belzutifan group vs 13·8 months [10·6 to not reached] in the everolimus group; hazard ratio 0·93 [95% CI 0·72 to 1·20]) and role functioning (median 12·0 months [9·2 to not reached] vs 10·2 months [4·7 to 14·4]; 0·88 [0·69 to 1·11]). INTERPRETATION: Belzutifan for advanced renal cell carcinoma was associated with improved disease-specific symptoms and QOL compared with everolimus. Taken together with the efficacy and safety data from LITESPARK-005, belzutifan could offer a clinical benefit without compromising the QOL of patients in this setting. FUNDING: Merck Sharp & Dohme, a subsidiary of Merck & Co, Rahway, NJ, USA.
Keywords: nádory ledvin; indeny; hodnocení výsledků péče pacientem; Humans; lidé středního věku; Quality of Life; Female; Aged; dospělí; senioři; lidé; doba přežití bez progrese choroby; kvalita života; Adult; ženské pohlaví; Male; Middle Aged; everolimus; karcinom z renálních buněk; Carcinoma, Renal Cell; Progression-Free Survival; mužské pohlaví; Everolimus; Kidney Neoplasms; Patient Reported Outcome Measures; Indenes